Funciones ejecutivas en el trastorno por déficit de atención e hiperactividad en niños. - Martínez Garzón, Cinthya Lizbeth (2024)
The present research is a bibliographic review that aims to analyze the executive functions in attention deficit hyperactivity disorder in children; the level of the research is descriptive, it had a population of 116 scientific publications belonging to the years 2014-2024 in Spanish, English, and Portuguese, the sample was non-probabilistic, made up of 41 scientific articles obtained from databases such as Pubmed, Google Scholar, Scielo, Redalyc, Elvieser and ScienceDirect. The methodological quality matrix (CRF-QS) was used to select the articles. Among the most relevant results, working memory is considered to be one of the most affected by EF. In conclusion, this evidence allows us to provide more information to parents with children with ADHD.